(untitled) (European Journal of Formal Sciences and Engineering, 2019)
The virtual learning environment is not just about taking a course and placing it on a computer, it deals with a combination of resources, interactivity, support and activities of structured learning. To carry out this process it is necessary to know the possibilities and limitations that the computer support or virtual platform offers us, so that the students achieve their study objective more adequately, for that reason its use is studied in the students of computer systems engineering career of the Tecnologico Nacional de Mexico, Campus Mexicali.